The Analysis of the Effect of Independence, Due Professional Care and Auditor Ethics on The Quality of Audit Results - Arum Ardianingsih; Amalia Ilmiani; Khaerul Umam (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
Examination of financial statements is a gradual process of activities that begin from planning, carrying out fieldwork audits and reporting quality of audit results. This study examines the dimensions of audit quality from the point of view of independence, due professional care and ethics of auditors on the quality of internal auditors of local governments in the ex Pekalongan residency. The analysis technique uses data quality test, classic assumption test and multiple linear regression analysis. Sampling technique with purposive sampling. Based on the analysis test, it was found that the independence, due professional care and ethics of auditors had a significant positive effect on the quality of audit results from internal auditors of the local government in the ex Pekalongan residency.